Tooth Loss and Perceived Masticatory Ability in Post-Menopausal Women - Riadiani, Bunga; Dewi, Ratna Sari; Ariani, Nina; Gita, Farisza (Journal of Dentistry Indonesia, 2014)
Post-menopausal women experience physiological hormonal changes that reduce bone density which leads to tooth loss and presumably affect masticatory function. Objective: This study aims to determine association between tooth loss and masticatory ability in post-menopausal women. Methods: Cross sectional study of 95 post-menopausal women at Posbindu Lansia Pergeri Depok, West Java was performed. Subjects answered questionnaires and intra oral examination was performed. Chi square analysis was conducted to relate age, menopausal period, education level, tooth loss and denture use with masticatory ability. Results: 47% subjects lost >10 teeth, 27% subjects lost 6-10 teeth and 26% subjects lost <0.05).